The Influence of Self Efficacy, Work Discipline and Organizational Culture On Job Satisfaction With An Impact On Employee Performance At PT. Unibles Indo Multi in South Jakarta - Moh. Sutoro (Universitas Dharma Wacana, 2022)
This study aims to determine the effect of self-efficacy, work discipline and organizational culture on job satisfaction which has an impact on employee performance at PT. Unables Indo Multi in South Jakarta. The method used is quantitative. The sampling technique used saturated sampling, amounting to 125 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, coefficient of determination analysis and hypothesis testing. The results of this study are self-efficacy has a significant effect on job satisfaction with a determination of 27.3%. Hypothesis test obtained t arithmetic > t table or (6.797 > 1.979) this is reinforced with a significance of 0.000 <0.05. Work discipline has a significant effect on job satisfaction with a determination value of 41.9%. Hypothesis testing obtained t arithmetic > t table or (9.412 > 1.979) this is reinforced with a significance of 0.000 <0.05. Organizational culture has a significant effect on job satisfaction with a determination value of 28.5%. Hypothesis test obtained t count > t table or (7.009 > 1.979) this is reinforced with a significance of 0.000 <0.05. Self-efficacy, work discipline and organizational culture simultaneously have a significant effect on job satisfaction with the regression equation Y = 6.428 + 0.221X1 + 0.416X2 + 0.218X3, the determination value is 51.7% while the remaining 48.3% is influenced by other factors. Hypothesis testing using statistical test F count > F table or (43.237 > 2.450), it is also reinforced with a significance of 0.000 <0.05. Job satisfaction has a significant effect on employee performance with a determination value of 38.96%. Hypothesis test obtained t arithmetic > t table or (8.846 > 1.979) this is reinforced with a significance of 0.000 <0.05